2008
DOI: 10.1029/2007jd009028
|View full text |Cite
|
Sign up to set email alerts
|

Systematic lidar observations of Saharan dust over Europe in the frame of EARLINET (2000–2002)

Abstract: More than 130 observation days of the horizontal and vertical extent of Saharan dust intrusions over Europe during the period May 2000 to December 2002 were studied by means of a coordinated lidar network in the frame of the European Aerosol Research Lidar Network (EARLINET). The number of dust events was greatest in late spring, summer, and early autumn periods, mainly in southern (S) and southeastern (SE) Europe. Multiple aerosol dust layers of variable thickness (300–7500 m) were observed. The center of mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
313
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(347 citation statements)
references
References 83 publications
28
313
0
6
Order By: Relevance
“…Given the low top altitude of the PBL and the strong marine layer above the PBL it can be concluded that the layer at 2.5 km is a pure dust layer with a lidar ratio of 70 sr, while the layer from 1.0 to 1.8 km contains dust, marine and anthropogenic particles (lidar ratio 40 to 50 sr). The lidar ratios agree well with the ones measured in (Papayannis et al, 2008). While DREAM forecast the dust entering Ireland's atmosphere on the 23 rd of April, the event was measured 30 hr before the model prediction.…”
Section: Resultssupporting
confidence: 73%
“…Given the low top altitude of the PBL and the strong marine layer above the PBL it can be concluded that the layer at 2.5 km is a pure dust layer with a lidar ratio of 70 sr, while the layer from 1.0 to 1.8 km contains dust, marine and anthropogenic particles (lidar ratio 40 to 50 sr). The lidar ratios agree well with the ones measured in (Papayannis et al, 2008). While DREAM forecast the dust entering Ireland's atmosphere on the 23 rd of April, the event was measured 30 hr before the model prediction.…”
Section: Resultssupporting
confidence: 73%
“…The results on the seasonal variability of occurrence of African dust events agree with previously published research. In particular, Papayannis et al (2008) found that the seasonal pattern of dust transport toward Europe is enhanced in the central and eastern Mediterranean during spring whereas Kallos et al (1998) and Rodriguez et al (2001) have shown that intrusions of Sahara dust in the region mainly occur during the winter and spring. Additionally, Remoundaki et al (2013) examined the PM 2.5 concentrations over Athens during 2010 and found the maximum, and with the most frequent abrupt changes, concentrations of elements which are typical constituents of dust (Si, Al, Ca, Fe, K, Mg, Ti) during spring and autumn.…”
Section: Contribution From African Dust Load To the Pm 10 Concentrationsmentioning
confidence: 99%
“…Sahara dust is transported over the Mediterranean Sea mainly because of the cyclone activity inside and around the area (Prospero, 1996). Papayannis et al (2005Papayannis et al ( , 2008 found that dust particles penetrate the geographical area located between 20-40°E and 40-47°N while the source region of desert dust for southern and south-eastern Europe is at the central and eastern Sahara regions. The long range transport of pollutants is induced by the different heating between the Mediterranean and Northern Africa, the land water contrast and the landscape variability (Kallos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dust outbreaks that reach western Europe occur mainly during the warm season from late spring to early autumn, as probed by lidar systems during the period May 2000-December 2002 (Papayannis et al, 2008). This generally happens with synoptic conditions characterized by the presence of a high-pressure region over Libya and a trough over the Bay of Biscay (e.g.…”
mentioning
confidence: 99%